2012
DOI: 10.1016/j.fishres.2011.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective accurate estimates of adult chum salmon, Oncorhynchus keta, abundance in a Japanese river using a radio-controlled helicopter

Abstract: This paper describes an attempt in 2008 to establish an aerial census of adult chum salmon using a small radio-controlled (RC) helicopter. The Moheji River, located in southern Hokkaido, was chosen because all the salmon in a stretch of the river between a weir and the estuary are seine-netted every morning for artificial propagation. Aerial photographs of the river were taken from a RC helicopter equipped with a digital single-lens reflex camera and polarized filter. To quantify salmon density within the cens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…The annual cost of UAS application exceeded the annual cost of a manned helicopter survey by $6817, but that cost differential cannot be applied across all studies. As a case in point, the estimated cost of counting Chum salmon within a small study area from a helicopter was about seven times higher than the cost observed for UAS application (Kudo et al 2012). Collecting data with a UAS also required federal authorization that was very difficult to understand and obtain during the 2012-2014 test years.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The annual cost of UAS application exceeded the annual cost of a manned helicopter survey by $6817, but that cost differential cannot be applied across all studies. As a case in point, the estimated cost of counting Chum salmon within a small study area from a helicopter was about seven times higher than the cost observed for UAS application (Kudo et al 2012). Collecting data with a UAS also required federal authorization that was very difficult to understand and obtain during the 2012-2014 test years.…”
Section: Discussionmentioning
confidence: 97%
“…The large body of wildlife literature reviewed by Linchant et al (2015) showed that counts made with a UAS are not always more accurate than counts made by other means (e.g., ground counts) as there was large variation in the accuracy comparisons reported. With regard to fish, Kudo et al (2012) used a UAS to count Chum salmon about once a week for 8 weeks and also seined and counted the fish weekly from the study area for comparison. The UAS count was lower than the seine count during 7 of the 8 weeks, but higher during 1 week.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spawning surveys for Chum Salmon O. keta and Sockeye Salmon O. nerka have been successfully conducted (Kudo et al. ; Whitehead et al. ).…”
mentioning
confidence: 99%